Anthology of Kumārilabhaṭṭa's works - Kumārila 600-660 (Motilal Banarsidass, 1980)
Selections from Ślokavārttika and Tantravārttika propounding Mīmāṃsā philosophy; includes a detailed study on his life and contribution.